Ireland / Level 2 - Vicary, Tim (Oxford ; New York : Oxford University Press, 2008)
"There are many different Irelands. There is the Ireland of peaceful rivers, green fields, and beautiful islands. There is the Ireland of song and dance, pubs and theatres - the country of James Joyce, Bob Geldof, and Riverdance. And there is the Ireland of guns, fighting, death, and the hope of peace. Come with us and visit all of these Irelands - and many more..." -- publisher's website
Includes glossary and exercises.
Keywords: Readers; Graded Reader Level 2; Readers (Adult); Readers for new literates; Reading comprehension -- Problems, exercises, etc; High interest-low vocabulary books; Ireland